Analisis Implementasi Kebijakan Mal Pelayanan Publik di Indonesia - Ariyanti, Aprilia Dwi; Simanjuntak, Jenius Hakim; Jafar, Muhammad Iqbal; Nugroho, Redo (Jurnal Informatika Ekonomi Bisnis, 2024)
Public service is an essential element in governance that aims to meet the needs of the community effectively. One of the significant innovations in Indonesia is the Public Service Mall (Mal Pelayanan Publik/MPP), which is an integrated service that integrates various types of services from the central government, local governments, business entities, and private sector in one location. Based on Presidential Regulation Number 89 of 2021, MPP aims to improve efficiency, accessibility, and quality of services, as well as encourage bureaucratic reform towards good governance. The implementation of MPP shows a positive impact in the form of reducing bureaucracy, time and cost efficiency, and increasing regional competitiveness. Vice President Ma'ruf Amin has given directions to implement MPP in all districts and cities. However, challenges still exist, such as institutional conditions both in terms of the One-Stop Investment and Integrated Services Agency (Dinas Penanaman Modal dan Pelayanan Satu Pintu/DPMPTSP) as the MPP coordinator and the service provider by organizations at the MPP, limited human resources, funding, and not all data between services are integrated. The analysis was conducted using a literature study method with data sources from books, journal articles that specifically discuss MPP in terms of policy implementation, legislative documents, reports, and other relevant sources and validated through interviews with the authors of the study related to the implementation of the MPP. The analysis was conducted using Grindle's policy implementation theory which combines the content of policy and the context of implementation, showing that the success of MPP is influenced by institutional support, commitment of related actors, adequate resources and must adjust to the conditions in which MPP policies are implemented. To ensure sustainability, institutional improvement, budget optimization, comprehensive evaluation, and the development of digital MPP as a future innovation are required. After implementing strategic steps, MPP has the potential to become a breakthrough solution in improving public services in Indonesia.